Strategi Political Marketing Partai Solidaritas Indonesia dalam Memperoleh Suara di DPRD Provinsi DKI Jakarta pada Pemilu 2019 - Andy Sanjaya; Iding Rosyidin (UIN Syarif Hidayatullah Jakarta, 2023)
Abstract. This study analyzes the political marketing strategy of DPW PSI Jakarta DPRD DKI Jakarta in the 2019 election. The purpose of this research is to look at PSI Jakarta's strategy in facing the 2019 election, so as to get 8 seats for DPRD DKI Jakarta. Also, to find out the obstacles faced by PSI Jakarta during the campaign. PSI's achievements as a new party have been quite successful and have even exceeded the expectations of its management. Even though it was full of controversy by carrying anti-corruption and anti-intolerance narratives which were labeled as anti-Islamic parties, it was able to get 8 seats. PSI as a new party, eventually made its way to the DKI Jakarta parliament. In this case, PSI's political marketing strategy is quite effective which is based on push, pull and pass political marketing. This study uses the main theory of political marketing. The focus of the discussion is PSI's political marketing strategy. The method used is qualitative, with interviews and documentation data collection techniques. Analysis of the research data is divided into three stages, namely data reduction, data presentation, and drawing conclusions. This research concludes that the political marketing strategy of DPW PSI Jakarta is quite effective. Meanwhile, the control is being branded as an anti-Islamic party, failing to pass the parliamentary threshold, and the eliteness of its narrative. Keywords: PSI, political marketing, strategy. Abstrak. Penelitian ini menganalisis tentang strategi pemasaran politik DPW PSI Jakarta DPRD DKI Jakarta pada pemilu 2019. Tujuan penelitian ini untuk melihat strategi PSI Jakarta dalam menghadapi pemilu 2019, sehingga mendapatkan 8 kursi untuk DPRD DKI Jakarta. Juga, untuk mengetahui kendala yang dihadapi oleh PSI Jakarta pada saat kampanye. Pencapaian PSI sebagai partai baru sudah cukup berhasil bahkan bisa melebihi ekspektasi dari para pengurusnya. Meski penuh kontroversi dengan mengusung narasi anti korupsi dan anti intoleransi yang dicap sebagai partai anti Islam, namun mampu mendapatkan 8 kursi. PSI sebagai partai baru, akhirnya melenggang ke parlemen DKI Jakarta. Dalam hal ini, strategi pemasaran politik PSI cukup efektif yang bertumpu pada push, pull dan pass political marketing. Penelitian ini menggunakan teori utama pemasaran politik. Fokus pembahasannya strategi pemasaran politik PSI. Metode yang digunakan adalah kualitatif, dengan teknik pengumpulan data wawancara dan dokumentasi. Analisis data penelitian ini terbagi menjadi tiga tahapan, yaitu reduksi data, penyajian data, dan penarikan kesimpulan. Penelitian ini menyimpulkan strategi pemasaran politik DPW PSI Jakarta cukup efektif. Sementara kendalnya adalah dicap partai anti Islam, tidak lolos parlementary threshold, dan keelitisan narasinya. Kata Kunci: PSI, marketing politik, strategi.